(untitled) (KYAMC Journal, 2024)
Background: Clinically significant sciatica due to disc prolapse occurs in 4-6% of the population. Among various options for the treatment of Prolapsed Lumber Intervertebral Disc (PLID) Pharmacotherapy, thermotherapy and exercise therapy are commonly used. Therapeutic exercises and ADL instruction can enable greater return of neurological function and improves long term outcome and quality of life. Objective: To see the effects of therapeutic exercises and ADL instructions on the treatment of PLID and their outcome. Materials and Methods: This prospective randomized clinical trial was performed over a period of six months on the patients of PLID. Evaluation was made at initial visit and follow up was done at third and sixth week by same investigator. In each visit pain intensity was seen by using straight leg raising test (SLR), Visual Analogue scale (VAS) respectively. Post intervention result was compared with baseline result. Results: The pain was mild in 11.4% cases of group A and 17.1% cases of group B (p=0.587). LBP was intermittent in most of the cases in both groups which was 71.4% cases and 80.0% cases in group A and group B respectively. Pain aggravates in most of the patient by walking (28.6%) and bending (21.3%) in both groups. However significant difference between group A and group B was found at week 6 follow up (p=<.005). During the study the SLR was improved significantly on week 6 follow up. The significant difference between group A and group B was found at week 6 follow up (p=<.005) regarding straight leg raising test (SLR) score. Conclusions: This study demonstrates the superiority of therapeutic exercises and activities of daily living in reduction of pain in management of patients with PLID. KYAMC Journal Volume: 15, No: 01, April 2024: 08-15.